Advances in structures required of polyphenols for xanthine oxidase inhibition - Liangliang Liu; Li Zhang; Licheng Ren; Yixi Xie (Food Frontiers, 2020)
Abstract Polyphenols have been used as natural medicaments for the management of hyperuricemia for a long history. They have been attracted many interests because of the little side effects in curing hyperuricemia, which is an important advantage over the antihyperuricemic drugs. In this review, the structure–activity relationships for polyphenols as xanthine oxidase (XO) inhibitors were discussed. It is concluded that the presence of hydroxyl groups, which influences the inhibitory effects, is closely related to whether the substitutions increase the steric hindrance or disturb the interaction of flavonoid with the catalytic site of XO, and the increased size of the molecule after glycosylation may increase the steric hindrance between flavonoid and XO, and consequently reducing the competitive inhibition behaviors. However, there is no obtained simple general rule that can comprehensively describe the effects of structural alteration on the inhibition activity because the results are varied among different subclasses of polyphenols. In addition, the inhibition mechanisms are mainly assumed as polyphenol binding to the active site of XO and hindering the entrance of xanthine or the discharge of uric acid and diffusion of O2− radical.